Application of optimized artificial intelligence algorithm to evaluate the heating energy demand of non-residential buildings at European level. (1st June 2019) - Ciulla, G.; D'Amico, A.; Lo Brano, V.; Traverso, M.
Abstract: A reliable preliminary forecast of heating energy demand of a building by using a detailed dynamic simulation software typically requires an in-depth knowledge of the thermal balance, several input data and a very skilled user. The authors will describe how to use Artificial Neural Networks to predict the demand for thermal energy linked to the winter climatization of non-residential buildings. To train the neural network it was necessary to develop an accurate energy database that represents the basis of the training of a specific Artificial Neural Networks. Data came from detailed dynamic simulations performed in the TRNSYS environment. The models were built according to the standards and laws of building energy requirements in seven different European countries, for 3 cities in each country and with 13 different shape factors, obtaining 2184 detailed dynamic simulations of non-residential buildings designed with high energy performances. The authors identified the best ANN topology developing a tool for determining, both quickly and simply, the heating energy demand of a non-residential building, knowing only 12 well-known thermo-physical parameters and without any computational cost or knowledge of the thermal balance. The reliability of this approach is demonstrated by the low standard deviation less than 5 kWh/(m 2 ·year). Graphical abstract: Image 1 Highlights: Alternative method to solve the building energy balance without any computational cost. Development of an ANN to assess of the energy performance of non residential building. Several dynamic models in different location with different shape factor were built TRNSYS. Implementation and creation of an organised energy database set.